A variação na concordância verbal com a primeira pessoa do plural em comunidades rurais do semiárido baiano - Carmo, Siméia Daniele Silva do (2016)
This dissertation is mainly aimed to do a mapping or not of occurrence of plural reading in the first person of existing verbs in spoken language in the Baiano semiarid region through a sociolinguistic analysis, checking which linguistic and sociocultural factors that contribute or not to this variation.We sought to investigate the hypothesis that there are patterns of variation and quantitative differences among the communities studied, due to: i) the ethnic background; ii) the community isolation and iii) the distance geographic area of the capital city, urbanization center. For this, it was taken as a research topic verbal agreement with the first person plural (P4) in rural communities of the Baiano semi-arid region, this topic has already been investigated by scholars as Silva (2003) and Lucchesi, Baxter and Silva (2009) which focused only in rural communities marked ethnically, Nina (1980), Almeida (2006), Araujo (2012), in addition to the descriptive analysis undertaken by dialectology scholars of the early twentieth century and by Veado (1982). Perceiving that the studies with the theme of the verbal agreement with P4 take, in most cases, as an example urban Brazilian Portuguese and also the study of pronominal switching (we / us), it is believed that this research becomes relevant because it is a work, in a way, unprecedented, once investigates rural speech and search to see specifically how the verb agreement is made with the first person plural in this variety. It drew up a comparative study between the dialects of the Baiano regions: Rio de Contas and Jeremoabo which according to social history are formed by black people (Barra / Bananal community) and white people (Mato Grosso community), located in the municipality communities of Rio de Contas; remaining Indians in Tapera community, Quilombo remnants in Casinhas community; mestizos and whites people in Lagoa do Inácio community, such communities are located in the municipality of Jeremoabo.In conclusion, the characterization of popular Portuguese of the country is marked by the socio-historical influence of each chosen community. Therefore, it can state that the verbal agreement is a variable phenomenon in the Baiano semi-arid region that it has gained trend towards the use of CV. Thus, it is used the theoretical - methodological model of Variationist Sociolinguistics it was found that the contact of ethnic groups, such as the isolation of some of them, resulted in linguistic differences, so that it can’t be ignored that formation of the popular Brazilian Portuguese language has its roots planted in the rural variety.